2016
DOI: 10.1186/s12864-016-3376-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic effects on tomato seed metabolic balance and its association with germination vigor

Abstract: BackgroundThe metabolite content of a seed and its ability to germinate are determined by genetic makeup and environmental effects during development. The interaction between genetics, environment and seed metabolism and germination was studied in 72 tomato homozygous introgression lines (IL) derived from Solanum pennelli and S. esculentum M82 cultivar. Plants were grown in the field under saline and fresh water irrigation during two consecutive seasons, and collected seeds were subjected to morphological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 112 publications
3
28
0
Order By: Relevance
“…4). The higher network connectivity of the cold-adapted accession Osl1, together with a higher ratio (~10 fold) of positive to negative correlations, supported the ability of Osl1 to adapt its metabolism at the initiation of the abiotic stress, similar to that observed in grapevine leaves 63 or tomato seeds 64 .…”
Section: Discussionsupporting
confidence: 62%
“…4). The higher network connectivity of the cold-adapted accession Osl1, together with a higher ratio (~10 fold) of positive to negative correlations, supported the ability of Osl1 to adapt its metabolism at the initiation of the abiotic stress, similar to that observed in grapevine leaves 63 or tomato seeds 64 .…”
Section: Discussionsupporting
confidence: 62%
“…For primary metabolite analysis, the temperature program was as follows: 1 min isothermal heating at 70°C, followed by a 1°C/min oven temperature ramp to 76°C, followed by a 6°C/min oven temperature ramp to 340°C, and a final 5 min heating at 340°C. Mass spectra were recorded at 1.6 scans per second with a mass-to-charge ratio of 70 to 550 scanning range [115]. Data acquisition was conducted by Mass Hunter software and the NIST mass spectral library.…”
Section: Metabolic Analysis Using Gas Chromatography-mass Spectrometrmentioning
confidence: 99%
“…Additionally, phytochromes can also act as important mediators of environmental cues (Donohue et al 2008). Several other studies indicated that the effect of the maternal environment can be mediated via seed provisioning | Chapter 1 (Zas et al 2013), the maternal tissues such as the seed coat (MacGregor et al 2015;Chen et al 2014b) as well as the accumulation of compounds such as storage proteins, metabolites and transcripts (Rosental et al 2016;He et al 2016;de Souza Vidigal et al 2016). The successful execution of the germination program does also depend on environmental conditions encountered by the seed shed from the mother plant.…”
Section: Environmental Regulation Of Seed Performancementioning
confidence: 99%
“…Upon imbibition, metabolic activity resumes, mobilizing stored metabolites to provide the basis for seed germination; an energy demanding process. As a result, the compounds stored in dry mature seeds reflect the process of seed maturation and can be linked to seed performance (Rosental et al 2014;Rosental et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation